Simulated ancient metagenomic ground truth dataset used for aMeta publication - Oskolkov, Nikolay (Stockholm University, 2022)
This is a simulated ancient metagenomic dataset used for benchmarking the anciemt microbiome profiling workflow aMeta against Heuristic Operations for Pathogen Screening (HOPS), see link under references. The dataset was simulated using gargammel software, see link under references. Both ancient and modern reads were simulated, sequencing errors and Illumina adapters were added. The simulated datase was built by Nikolay Oskolkov, Lund University, Sweden, within the NBIS SciLifeLab long-term support project, PI Anders Götherström, Centre for Palaeogenetics, Stockholm, Sweden.
Keywords: Bioinformatic methods development; Medical and Health Sciences; Medicin och hälsovetenskap; Bioinformatics (Computational Biology); Bioinformatik (beräkningsbiologi)